Hydroarylations by cobalt-catalyzed C–H activation - Rajagopal Santhoshkumar; Chien-Hong Cheng (Beilstein Journal of Organic Chemistry, 2018)
As an earth-abundant first-row transition metal, cobalt catalysts offer a broad range of economical methods for organic transformations via C–H activation. One of the transformations is the addition of C–H to C–X multiple bonds to afford alkylation, alkenation, amidation, and cyclization products using low- or high-valent cobalt catalysts. This hydroarylation is an efficient approach to build new C–C bonds in a 100% atom-economical manner. In this review, the recent developments of Co-catalyzed hydroarylation reactions and their mechanistic studies are summarized.